2017
DOI: 10.4274/jcrpe.4456
|View full text |Cite
|
Sign up to set email alerts
|

Response to Growth Hormone Treatment in a Patient with Insulin-Like Growth Factor 1 Receptor Deletion

Abstract: We report a six-year-old boy who presented with short stature, microcephaly, dysmorphic features, and developmental delay and who was identified with a terminal deletion of 15q26.2q26.3 containing the insulin-like growth factor receptor (IGF1R) gene in addition to a terminal duplication of the 4q35.1q35.2 region. We compare our case with other reports of deletions and mutations affecting the IGF1R gene associated with pre-and postnatal growth restriction. We report the dramatic response to growth hormone thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Also the c.1549A > T, the p.Y487F mutation was reported in a patient with microcephaly and prenatal and postnatal growth impairment [ 24 ]. GH treatment of a patient with short stature, microcephaly, dysmorphic features, developmental delay and a terminal deletion of 15q26.2q26.3 containing the IGF1R gene in addition to a terminal duplication of the 4q35.1q35.2 region resulted in a strong growth response [ 25 ]. It is of note that the GH treatment in our patients had mixed effects.…”
Section: Discussionmentioning
confidence: 99%
“…Also the c.1549A > T, the p.Y487F mutation was reported in a patient with microcephaly and prenatal and postnatal growth impairment [ 24 ]. GH treatment of a patient with short stature, microcephaly, dysmorphic features, developmental delay and a terminal deletion of 15q26.2q26.3 containing the IGF1R gene in addition to a terminal duplication of the 4q35.1q35.2 region resulted in a strong growth response [ 25 ]. It is of note that the GH treatment in our patients had mixed effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several alterations (point mutations and deletions) in the IGF1 and insulin-like growth factor 1 receptor ( IGF-1R ) genes have been demonstrated last decade. Alterations have been identified that affect IGF1R biosynthesis, signal reception and receptor kinase activity [ 9 ] [ 10 ] [ 11 ] [ 12 ] [ 13 ] [ 14 ] [ 15 ] [ 16 ] [ 17 ] [ 18 ] [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the response to conventional growth hormone (GH) therapy in patients with IGF-1R and IGF-1 mutations is notably variable (8). While some patients demonstrate a good growth response (8)(9)(10), others show little to no improvement (11,12).…”
Section: Introductionmentioning
confidence: 99%